Actitud hacia las matemáticas del alumnado del grado en administración - Tugores, Laia; Raposo-Rivas, Manuela (Góndola, enseñanza y aprendizaje de las ciencias, 2026)
Students’ attitudes toward mathematics directly influence their learning. The aim of this study is to examine how mathematics is perceived by students enrolled in the Bachelor’s Degree in Business Administration and Management. To this end, their experiences, stereotypes, and beliefs are analyzed; their views on the role of teachers are collected; and their levels are assessed across four attitudinal dimensions: anxiety, confidence, enjoyment, and perceived usefulness. The study also considers discriminating variables such as gender, prior educational background, grades in the subject, and any support received to overcome difficulties. The research methodology is both descriptive and mixed. The data collection instrument is a self-developed questionnaire, consisting of 32 items and 4 open-ended questions. The study population consists of 126 first-year students enrolled in the Bachelor’s program at the University of Vigo in Ourense. The sample comprises 90 students who voluntarily and anonymously completed the printed questionnaire. The Cronbach's alpha values are: .768 for anxiety, .622 for confidence, .763 for enjoyment, and .736 for usefulness. The variable of whether or not a student has ever failed Mathematics produces the most significant differences. Men are more likely than women to believe that "mathematics is only for intelligent people" and that "men generally have greater mathematical intelligence than women," whereas exams provoke greater anxiety in women. It is concluded that there are notable similarities and discrepancies compared to other studies on students' attitudes toward mathematics.